Sirtuin Family and Diabetic Kidney Disease - Bian, Che; Ren, Huiwen (Frontiers in Endocrinology, 2022)
Diabetes mellitus (DM) is gradually attacking the health and life of people all over the world. Diabetic kidney disease (DKD) is one of the most common chronic microvascular complications of DM, whose mechanism is complex and still lacks research. Sirtuin family is a class III histone deacetylase with highly conserved NAD+ binding domain and catalytic functional domain, while different N-terminal and C-terminal structures enable them to bind different deacetylated substrates to participate in Cellular NAD+ metabolism. The kidney is an organ rich in NAD+, and database exploration shows that the Sirtuin family has different expression localization in renal, cellular and subcellular structures from literature. With the progress of modern technology, a variety of animal models and reagents for the Sirtuin family and DKD emerged. Machine learning in the literature shows that the Sirtuin family can regulate pathophysiological injury mainly in glomerular filtration membrane, renal tubular absorption, and immune inflammation through various mechanisms such as epigenetics, multiple signaling pathways, and mitochondrial function. These mechanisms are the key nodes participating in DKD. Thus, it is of great significance for target therapy to study biological functions of the Sirtuin family and DKD regulation mechanism in-depth.